2006
DOI: 10.1111/j.1445-5994.2006.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication deficiencies in research and monitoring by ethics committees

Abstract: Improvements are necessary in the communication between ethics committees and researchers and research participants, and there is a need for more effective monitoring by ethics committees of research practices. The questionnaire designed for this study could be applied in a prospective manner as a useful tool for monitoring the conduct of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
6
0
3
Order By: Relevance
“…Borracci et al 8 evaluated 100 authors of studies presented at the Argentinean Congress of Cardiology and verified that only 36.0% of them had submitted their studies to ethical review. Karunaratne et al 9 interviewed research subjects, researchers and members of REC in Australia to evaluate the communication deficiencies and research monitoring. They reported that 6.0% of the researchers believed that the FICF was not necessary, 44.0% of the research subjects were not informed on the existence of ethical committees and 12.0% of the researchers believed that the quality of research monitoring could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Borracci et al 8 evaluated 100 authors of studies presented at the Argentinean Congress of Cardiology and verified that only 36.0% of them had submitted their studies to ethical review. Karunaratne et al 9 interviewed research subjects, researchers and members of REC in Australia to evaluate the communication deficiencies and research monitoring. They reported that 6.0% of the researchers believed that the FICF was not necessary, 44.0% of the research subjects were not informed on the existence of ethical committees and 12.0% of the researchers believed that the quality of research monitoring could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Por lo tanto, un monitoreo es un proceso sistemático, independiente y documentado para obtener evidencias y evaluarlas de manera objetiva, a fin de determinar el alcance para que los requisitos se cumplan. Lo anterior implica la realización de actividades de evaluación, seguimiento y mejoramiento de los procesos definidos como prioritarios; la comparación entre la calidad observada y aquella esperada, misma que debe estar previamente definida mediante guías y normas técnicas, científicas y administrativas; la adopción, por parte de las instituciones, de medidas tendentes a corregir las desviaciones detectadas con respecto a los parámetros previamente establecidos, así como a mantener las condiciones de mejora realizadas (8,(19)(20)(21)(22)(23)(24). El objeto del monitoreo de un estudio es verificar que (8,20):…”
Section: ¿Qué Es El Monitoreo De Estudios?unclassified
“…Aunque en la literatura el término monitoreo parece referirse casi exclusivamente al control de la calidad de los datos de los ensayos clínicos con medicamentos (11,15,20,22,25,26), las BPC y otros autores proponen que se aplique a todas las investigaciones en salud humana independientemente de su diseño, del enfoque metodológico o del riesgo ético del estudio (7,8,17,19,24,(27)(28)(29)(30)(31).…”
Section: Alcance Y Naturaleza Del Monitoreounclassified
See 1 more Smart Citation
“…There is good information from Australia on conflicts of interest 6 and research ethics committees 18,19 with respect to the practice of research involving investigators and the pharmaceutical industry. However, there is little information or data explicitly dealing with access and attitudes to, or use of, ethical Guidelines for interactions with industry by medical professionals.…”
Section: Introductionmentioning
confidence: 99%